Eficiência de adjuvante potencializador de herbicida no manejo de dessecação pré plantio - Motta, Eduardo Gabriel Ferreira (2024)
Brazilian agricultural production is extremely important both nationally and internationally due to the high demand for food. However, it is an activity full of risks and challenges, especially since it involves outdoor production. One of the main issues in agricultural production is the competition between desired crops and invasive plants. After adopting soil conservation practices, such as no-till farming, the use of herbicides has become the main strategy for controlling these invasive plants. In this context, various products have emerged on the market, including those that do not directly affect plants but improve the application conditions of herbicide solutions, known as adjuvants. This study aimed to analyze the efficiency of the HT-35 (Incrop) adjuvant enhancer and the pre-planting desiccation management. The research was conducted in the experimental area of UTFPR, Dois Vizinhos campus, in November 2023. Four different management approaches were tested, duplicated to assess with and without the enhancer, totaling eight treatments. These were further duplicated to evaluate two different sequential products, diquat and glufosinate-ammonium, resulting in 16 treatments and a control. The experiment followed a randomized block design with three replications, and treatments were applied using a backpack sprayer. Weed control evaluations were carried out at 7, 14, and 21 days after application (DAA). Treatments with glyphosate + haloxyfop-p-methyl + halauxifen-methyl/diclosulam (T1, T2, T9, T10), saflufenacil + glyphosate (T7, T8, T15, T16), and 2,4-D + glyphosate (T3, T4, T11, T12) showed the highest control percentages (above 80%) at the end of the evaluation period. The least effective treatments were those using halauxifenmethyl/diclosulam (Paxeo) alone, with control rates below 50%. There were no statistically significant differences between treatments with and without the enhancer, and no significant differences were found between sequential treatments with diquat and glufosinate-ammonium. Further studies under different conditions and management practices are necessary to confirm the efficiency of the tested product.